Controller Evaluation Technique Using Virtual Test Model in Shaking Tables - KAJIWARA, Kouichi; TAGAWA, Yasutaka; NAGAI, Eiji; SATO, Eiji (Transactions of the Japan Society of Mechanical Engineers Series C, 2006)
In control system design for shaking tables, it is well known that many experiments have to be done to find a suitable controller. However, control experiments with a test model on the shaking table are sometimes very difficult especially for a large shaking table, because they are expensive to construct and install on the shaking table. If the test model dynamics can be taken into consideration without using the real test model, these experiments cost much less than the experiments with a real test model. Hence, this study proposes a controller evaluation technique using a virtual test model, instead of using the real test model. Furthermore, effectiveness of this technique is verified through both simulations and experiments using a 3DOF shaking table.